A novel computer navigation model guided unilateral percutaneous vertebroplasty for vertebral compression fracture: A case report. Issue 44 (30th October 2020) - Xu, Hao-Tian; Zheng, Shuang; Kang, Ming-Yang; Yu, Tong; Zhao, Jian-Wu
Abstract: Rational: Vertebral compression fracture (VCF) is one of the most common diseases in spinal surgery. Traditional percutaneous vertebroplasty (PVP) under fluoroscopy is an effective method to treat vertebral compression fracture. However, there is still a risk of vascular nerve injury and infection caused by inaccurate or repeated puncture. Therefore, the purpose of this paper was to assess the accuracy of unilateral PVP guided by screw view model of navigation (SVMN) for VCF. Patient concerns: A 59-year-old female patient suffered high falling injury, and with back pain as its main clinical symptom. Diagnoses: The patient was diagnosed with a L1 VCF. Interventions: We placed the puncture needle under the guidance of SVMN to reach the ideal position designed before operation, and then injected the bone cement to complete the percutaneous kyphoplasty (PKP). Outcomes: The operative time was 29.5 minutes, the puncture time was 1 time, the fluoroscopy time was 2.9 minutes, and the bone cement distribution was satisfactory. VAS and ODI scores were significant improved postoperatively. No surgical complications, including neurovascular injury and infection, were observed during 28-month follow up. Lessons: The SVMN guided percutaneous puncture needle insertion in PKP operation for VCF is an effective and safety technique. Besides, the SVMN has also been a contributor to reduce radiation doses and replace conventional fluoroscopy.